Manhaju Tauthīq Mutūn al-Ḥadīth ‘inda ‘uṣulīya al-‘aḥnāf - Samsul Anwar (Al-Jami'ah: Journal of Islamic Studies, 2000)
This article discusses the method of evaluating the authenticity of hadits, based on the internal criticism which was applied by the scholars of Hanafi School. In this writing, it is mentioned that the scholars have developed five criteria for examining a hadits. First a hadits does not contradict Qur' anic texts. This leads the Hanafi School to refuse takhṣīṣ and taqyīd theories of al-Qur'an with ahad hadits. Second, a hadits is not contrary to a popular sunnah (masyhūr). Under this criterion, they avoided confronting a ḥadīts with each other in order to seek in their consistency; third, a ḥadīts is not garīb (isolating) if it is connected to usual and common case. Fourth, a ḥadīts is not abandoned by the Companions in their discussion. Finally, a ḥadīts must in agreement with (analogies) general rule of syari' ah if it contains legal matters, but was reported by the authority of a non-expert in law. The ḥadīts which do not meet with the five criteria are considered inauthentic. Compared to the traditionalist school that focuses more on the authority of ḥadīts reporters, the Hanafi School is more critical of the ḥadīts.